The Utilization of Financial Models in The Study of The Profitability of Photovoltaic Investments in Polish Conditions - Mariusz CHUDZICKI (Communications of International Proceedings, 2021)
The following article presents the problems related to the profitability of photovoltaic installations using the abilities of financial modeling. Financial models allow you to study the profitability of various different solutions in each economic area, including investments in photovoltaic installations. The dynamic development of the photovoltaic installations sector has generated problems, the greatest of which is the storage of produced energy. In this article, an attempt was made to assess the economic justification for the creation of home energy storage and their profitability in the current economic conditions. The optimal storage is one that gives the household complete energy independence, but as it has been shown in the published research results, such a solution, although technically possible, is completely unprofitable in today's economic conditions. Research has shown that even a twofold increase in self-energy consumption thanks to storage from 30% to 60% requires such expenditure that cannot be outweighed by the resulting benefits. Currently, the use of solutions consisting in delivering surplus energy to the grid is the most economically justified, however, a further increase in energy prices, and a change in the rules of accounting for surpluses, from annual to monthly periods, may increase the profitability of energy storage. The factor that will increase the popularity of energy storage will probably be the decline in their prices.
Keywords: Photovoltaic Installation; Financial Models; Investment’s Profitability